Trilobatin Protects Against Aβ25–35-Induced Hippocampal HT22 Cells Apoptosis Through Mediating ROS/p38/Caspase 3-Dependent Pathway - Chen, Nana; Wang, Jiao; He, Yuqi; Xu, Yingshu; Zhang, Yuchuan; Gong, Qihai; Yu, Changyin; Gao, Jianmei (Frontiers in Pharmacology, 2020)
Emerging evidence reveals that an aberrant accumulation of β-amyloid (Aβ) is the main reason of Alzheimer's disease (AD) pathogenesis. Thus inhibition of Aβ-induced neurotoxicity may be promising therapeutic tactics to mitigate AD onset and advance. The development of agent candidates by cultured neurons against Aβ-induced cytotoxicity is widely accepted to be an efficient strategy to explore the drug for AD patients. Previously, we have revealed that trilobatin (TLB), a small molecule monomer, derives from Lithocarpus polystachyus Rehd, possessed anti-oxidative activities on hydrogen peroxide-induced oxidative injury in PC12 cells. The present study was designed to investigate the effects and further to explore the potential underlying mechanism of TLB on Aβ-induced injury in hippocampal HT22 cells. The results demonstrated that TLB attenuated Aβ25–35-induced HT22 cell death, as evidenced by MTT assay and LDH release. Furthermore, TLB dramatically mitigated cell death after Aβ25–35 insult via decreasing the intracellular and mitochondrial ROS overproduction and restoring anti-oxidant enzyme activities, as well as suppressing apoptosis. Of note, Aβ25-35-induced increase in ratio of Bax/Bcl-2, activation of caspase-3, phosphorylation of p38 MAPK, and decrease in Sirt3 expression were suppressed by TLB, as evidenced by Western blot analysis. Intriguingly, TLB could directly bind to p38, as evidenced by molecular docking. Taken together, the results reveal that TLB effectively protects against Aβ25–35-induced neuronal cell death via activating ROS/p38/caspase 3-dependent pathway. Our findings afford evidence for the potential development of TLB to hinder neuronal death during AD.